Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s13201-021-01505-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of temperature alteration on the drinking water quality stored in plastic bottles

Abstract: Many people prefer to drink bottled water instead off the tap water. The bottled water is stored in the plastic bottles sometimes for long time. These plastic bottles might leach out some harmful materials into the water especially when exposed to temperature alteration, which may affect human health. This research work focused on investigating the effect of changing temperature on the bottled water quality. The work studied the effect of heating water in plastic bottles by sun, oven, and microwave. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Results showed that there was no statistically significant difference in DMP and DEHP concentrations at specific times among samples stored indoors and outdoors with pvalues of 0.549 and 0.077 respectively (Table 8). This illustrates how temperature, whether indoors or outdoors, influences a number of the physical properties of drinking water, such as its density, viscosity, decreasing the values of total dissolved substance(TDS), alkalinity, and dissolved chemical content [35].…”
Section: The Effects Of Storage Conditions On Pae Concentration Levelsmentioning
confidence: 99%
“…Results showed that there was no statistically significant difference in DMP and DEHP concentrations at specific times among samples stored indoors and outdoors with pvalues of 0.549 and 0.077 respectively (Table 8). This illustrates how temperature, whether indoors or outdoors, influences a number of the physical properties of drinking water, such as its density, viscosity, decreasing the values of total dissolved substance(TDS), alkalinity, and dissolved chemical content [35].…”
Section: The Effects Of Storage Conditions On Pae Concentration Levelsmentioning
confidence: 99%
“…; sunlight and moisture). In a research study conducted by Ahmed et al [25], where they investigated the potential effects of temperature change on bottled water quality, the temperature changes resulted in changes in the physicochemical properties of bottled water. Qiao et al [26] investigated the storage habits of polyethylene terephthalate (PET) bottled drinking water during summer in laboratory and car trunks.…”
Section: Microplastics In Single Use Bottlesmentioning
confidence: 99%
“…Additionally, it was found that water from a residential RO device had a greater negative impact on climate change and the use of fossil fuels than water from a commercial RO device. Ahmed et al (2021) examined how temperature variations affect the caliber of bottled water. They investigated what happened when they froze and cooled bottled water and when they heated the water in plastic bottles in the sun, oven, and microwave.…”
Section: Bottled Watermentioning
confidence: 99%
“…The most suitable study area in such circumstances is where people consume bottled water and tap water. A recent surge has been observed in bottled water consumption in Jinnahabad (Ahmed et al, 2021;Ahmed et al, 2020), making it a suitable area for site selection and water alternatives comparison.…”
Section: Site Identificationmentioning
confidence: 99%